PENGARUH LAJU PERTUMBUHAN SEKTOR INDUSTRI, INVESTASI DAN UPAH TERHADAP PENYERAPAN TENAGA KERJA SEKTOR INDUSTRI DI KABUPATEN ASAHAN - Denny Permana Siregar; Nurbaiti Nurbaiti; Khairina Tambunan (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2022)
This study was conducted to determine how the effect of the growth rate of industrial sector, investment and wages on industrial sector employment in Asahan Regency. This study uses secondary data obtained from the official website of the Central Bureau of Statistics of Asahan Regency and Investment Coordinating Board of the Republic of Indonesia. Analysis that used is descriptive quantitative with multiple linear regression analysis model. The dependent variable used is industrial sector employment. While the independent variable used is the growth rate of industrial sector, investment and wages. In this research, Eviews 10 software is used as an estimation tool. The results showed that the growth rate of industrial sector has a negative and significant effect on employment in the industrial sector, the investment variable has a negative and significant effect on employment in the industrial sector and wage variables has a positive and significant effect on employment in the industrial sector. The results of this study also show that the coefficient of determination is 0.982244 which means the employment in the industrial sector in Asahan Regency can be explained by the growth rate of industrial sector, investment and wages variables factor by 98.22%. While the remaining 1.78% is explained by other variables not examined in this study.